2018
DOI: 10.1038/s41431-018-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep phenotyping of speech and language skills in individuals with 16p11.2 deletion

Abstract: Recurrent deletions of a ~600-kb region of 16p11.2 have been associated with a highly penetrant form of childhood apraxia of speech (CAS). Yet prior findings have been based on a small, potentially biased sample using retrospectively collected data. We examine the prevalence of CAS in a larger cohort of individuals with 16p11.2 deletion using a prospectively designed assessment battery. The broader speech and language phenotype associated with carrying this deletion was also examined. 55 participants with 16p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 40 publications
2
59
0
5
Order By: Relevance
“…Moderate ID, ASD, poor cognitive and language ability (as great as 2 standard deviation below familial non‐carriers), epilepsy, macrocephaly (apparent by age 2 years), brain abnormalities such as Chiari type 1 malformations or cerebellar ectopia and obesity are associated with 16p11.2 deletion . Several studies have also confirmed the high penetrance of CAS in children with 16p11.2 deletions . Other speech profiles have also been reported in 16p11.2 deletion in addition to CAS, including articulation and phonological disorders, dysarthria, minimal verbal output and even typical speech in some …”
Section: Genetic Bases Of Casmentioning
confidence: 72%
See 4 more Smart Citations
“…Moderate ID, ASD, poor cognitive and language ability (as great as 2 standard deviation below familial non‐carriers), epilepsy, macrocephaly (apparent by age 2 years), brain abnormalities such as Chiari type 1 malformations or cerebellar ectopia and obesity are associated with 16p11.2 deletion . Several studies have also confirmed the high penetrance of CAS in children with 16p11.2 deletions . Other speech profiles have also been reported in 16p11.2 deletion in addition to CAS, including articulation and phonological disorders, dysarthria, minimal verbal output and even typical speech in some …”
Section: Genetic Bases Of Casmentioning
confidence: 72%
“…Almost all children with KdVS receive a diagnosis of CAS, which is often comorbid with dysarthria and additional articulation and phonological errors . The presence of CAS with co‐occurring speech diagnoses is seen in other genetic conditions, such as Floating‐Harbor syndrome, 7q11.23 duplication syndrome, 16p11.2 deletion and 2p15p16.1 microdeletion as noted above …”
Section: Genetic Bases Of Casmentioning
confidence: 91%
See 3 more Smart Citations